From Relaxed Beliefs Under Psychedelics (REBUS) to Revised Beliefs After Psychedelics (REBAS): preliminary development of the RElaxed Beliefs Questionnaire (REB-Q) - Zeifman,R; Spriggs,M; Kettner,H; Lyons,T; Rosas,F; Mediano,P; Erritzoe,D; Carhart-Harris,R (PsyArXiv, 2022)
Background: The Relaxed Beliefs Under pSychedelics (REBUS) model proposes that serotonergic psychedelics decrease the precision weighting of neurobiologically-encoded beliefs, and offers a unified account of the acute and therapeutic action of psychedelics. Although REBUS has received some neuroscientific support, little research has examined its psychological validity. We conducted a preliminary examination of two psychological assumptions of REBUS: (a) psychedelics foster acute relaxation and post-acute revision of confidence in mental-health-relevant beliefs; (b) this relaxation and revision facilitates positive therapeutic outcomes and is associated with the entropy of EEG signals (an index of neurophysiological mechanisms relevant to REBUS). Method: Healthy individuals (N=11) were administered 1 mg and 25 mg psilocybin 4-weeks apart. Confidence ratings for personally held negative and positive beliefs were obtained before, during, and 4-weeks after dosing sessions. Acute entropy and self-reported subjective experiences were measured, as was well-being (before and 4-weeks after dosing sessions). Results: Confidence in negative self-beliefs decreased following 25 mg psilocybin and not following 1 mg psilocybin. Entropy and subjective effects under 25 mg psilocybin correlated with decreases in negative self-belief confidence (acute and 4-weeks after dosing). Particularly strong evidence was seen for a relationship between decreases in negative self-belief confidence and increases in well-being at 4-weeks. Conclusions: We report the first empirical evidence that the relaxation and revision of negative self-belief confidence mediates positive psychological outcomes; a psychological assumption of REBUS. Replication within larger and clinical samples remains necessary. We also introduce a new measure, the Relaxed BEliefs Questionnaire (REB-Q), for examining the robustness of these preliminary findings and the utility of the REBUS model.